Efficacy of Acute Intermittent Hypoxia on Physical Function and Health Status in Humans with Spinal Cord Injury: A Brief Review - Todd A. Astorino; Eric T. Harness; Ailish C. White (Neural Plasticity)
Spinal cord injury (SCI) results in a loss of motor and sensory function and is consequent with reductions in locomotion, leading to a relatively sedentary lifestyle which predisposes individuals to premature morbidity and mortality. Many exercise modalities have been employed to improve physical function and health status in SCI, yet they are typically expensive, require many trained clinicians to implement, and are thus relegated to specialized rehabilitation centers. These characteristics of traditional exercise-based rehabilitation in SCI make their application relatively impractical considering the time-intensive nature of these regimens and patients’ poor access to exercise. A promising approach to improve physical function in persons with SCI is exposure to acute intermittent hypoxia (IH) in the form of a small amount of sessions of brief, repeated exposures to low oxygen gas mixtures interspersed with normoxic breathing. This review summarizes the clinical application of IH in humans with SCI, describes recommended dosing and potential side effects of IH, and reviews existing data concerning the efficacy of relatively brief exposures of IH to modify health and physical function. Potential mechanisms explaining the effects of IH are also discussed. Collectively, IH appears to be a safe, time-efficient, and robust approach to enhance physical function in chronic, incomplete SCI.